Studi etnomatematika: Konsep geometri matematika pada kerajinan gerabah - Pardi, M. Habib Husnial; Mubarok, Lutfi (Jurnal of Math Tadris, 2024)
The purpose of this study was to determine the concept of mathematical geometry found in the pottery craft of Banyumulek Village and the form of relevant math problems based on the concept of mathematical geometry found. This research uses a qualitative approach with ethnography type. The data collection methods used were observation, interview, and documentation. This research was conducted in Banyumulek Village, Kediri District, West Lombok, NTB. The results showed that in pottery (plate, glass, cobek, kekete, jug, selao, perapen, penyiong kupi, flower pot) there is a concept of mathematical geometry in some of the pottery, namely: curvilinear and flat geometry. The concept of geometry of flat circular shapes is found on the base of the plate, glass, cobek and the top of the jug and selao. While the tube shape is found on the glass, the hemispherical shape on the kekete and penyiong kupi, the cone shape is truncated on the selao, jug, and flower pot. The relevant form of mathematical problems is found in the geometry of spatial shapes in grade IX SMP / MTs, while flat shapes are found in grades VII and VIII SMP / MTs.